Experimental Analysis of an Innovative Double Strap Joint Splicing of GFRP Bars by NSM Methods for Strengthening RC Beams - Ranković, Slobodan; Folić, Radomir; Zorić, Andrija; Vacev, Todor; Petrović, Žarko; Kovačević, Dušan (Periodica Polytechnica Civil Engineering, 2024)
The double strap joint splicing of glass fiber reinforced polymer (GFRP) bars for reinforced concrete (RC) beams strengthening, applying the near surface mounting (NSM) method, has been proposed in the paper. The proposed method consists of application of the supplementary GFRP bars symmetrically positioned in the cut-off zone of the main GFRP reinforcement. The performances of this splicing method have been experimentally tested for the most unfavorable case of the GFRP reinforcement cut-off in the maximal bending moment zones. During the experiment, the varied parameter has been overlapping length of the bars, taking values of 20∅ and 40∅. Evaluation of the splicing technique is done comparing the experimental results with the results of the behavior of beams strengthened by GFRP bars without cut-off and with cut-off, but without splicing. Experimental research encompassed analysis of strength, stiffness, ductility, crack pattern, strains in the steel, GFRP reinforcement and concrete, and the failure modes of the beams. It has been shown that in case of the cut-off of the GFRP bar, strengthening effectivity decreases for 39%, and that in the case of bypassing the cut-off using double strap 20∅ and 40∅ long, strengthening effectivity decreased 23%, and 14% respectively, compared to the beam without GFRP bar cut-off. Using extrapolation, it has been shown that double strap with length of 60∅ provided strength equivalent to the case without cut-off. The result of application of this splicing method of the additional GFRP bars is significant increase of strength and serviceability of the strengthened RC beams.